Postprandial elevation of tissue factor antigen in the blood of healthy adults - Motton, Deborah D.; Mackman, Nigel; Tilley, Rachel E.; Rutledge, John C. (Thrombosis and Haemostasis, 2005)
Atherosclerosis is a dynamic disease involving lipid metabolism, inflammation and thrombosis. A key factor in thrombosis is tissue factor, a small transmembrane glycoprotein. Tissue factor binds FactorVIIa, and this complex converts Factor X to Factor Xa, leading to thrombin generation and fibrin formation. Inhibition of this pathway is by tissue factor pathway inhibitor (TFPI). Tissue factor is found sequestered within atherosclerotic plaques, and plaque rupture allows tissue factor exposure to the circulation, leading to formation of a thrombus. Tissue factor is also associated with membrane microparticles in the circulation, most likely released from monocytes activated by an inflammatory event. We hypothesize that consumption of a typical western diet that is moderate in fat content leads to elevated levels of circulating tissue factor that may act as a marker of a pro-thrombotic state. Healthy volunteers, aged 18-55, consumed a moderate (40%) fat meal, with blood taken before and 3.5 and 6 h after the meal. Plasma was isolated and assayed for plasma triglycerides, tissue factor, thrombin antithrombin (TAT) complexes, TFPI and TNFα. The levels of circulating tissue factor increased 56% (from 78 pg/ml to120 pg/ml) 3.5 h after the meal. Levels decreased, but had not returned to baseline 6 h postprandially. No significant differences in TAT, TFPI and TNFá levels were observed postprandially. These results demonstrate increased tissue factor levels in individuals who consumed a moderate fat diet. This suggests that the typical western diet may play a larger role in cardiovascular disease than merely altering lipid profiles.
Keywords: Tissue factor; postprandial lipemia; diet; atherosclerosis